Integrative approaches to depression in end-stage renal disease: insights into mechanisms, impacts, and pharmacological strategies - Yuan, Cheng; Chang, Fengpei; Zhai, Hongfu; Du, Jiayin; Lu, Danqin; Ma, Haoli; Wu, Xiaoyan; Gao, Ping; Ni, Lihua (Frontiers in Pharmacology, 2025)
Depression is a frequently overlooked psychiatric symptom in patients with end-stage renal disease (ESRD), seriously affecting their quality of life, risk of death, adherence to treatment, cognitive abilities, and overall health outcomes. The study investigates the prevalence of depression is in ESRD patients, along with the methods for assessment, diagnostic guidelines, underlying factors, consequences, and management strategies. The Beck Depression Inventory (BDI), with an optimal diagnostic cutoff score greater than 14, has been identified as the most accurate for diagnosing depression in ESRD, while emerging tools such as vacancy-driven high-performance metabolic assays show promise for evaluation. Depression contributes to adverse health outcomes by increasing risks of treatment withdrawal, suicide, and cognitive impairment, as well as serving as a predictor of mortality and poor treatment adherence. Even though tricyclic antidepressants and selective serotonin reuptake inhibitors are commonly used, the effectiveness of treatment remains unpredictable because clinical studies often have limitations such as small sample sizes, no randomization, and missing control groups. Innovative approaches, such as nanomaterials and traditional Chinese medicine, have shown therapeutic potential with reduced side effects. Future research should focus on specific high-risk populations, particularly older adults and women under the age of 45, to better tailor interventions. The goal of this research is to improve understanding of depression in ESRD, leading to better patient care, improved quality of life, and superior clinical results.